The combined effect of Weisella cibaria and Fusarium oxysporum nanoparticles on cervical cancer cells (Baghdad Science Journal, 2024)
The predicted global cancer burden is expected to surpass 20 million new cancer cases by 2025. Despite recent advancements in tumor therapy, successful cancer treatment remains challenging. The emerging field of nanotechnology offers great opportunities for diagnosis, imaging, as well as treatment of cancer. The biosynthesis of silver nanoparticles by fungi is an ecologically clean and nontoxic method compared to other physical and chemical methods. The purpose of this study is to determine the Synergistic Effect of Combination Nanoparticles Synthesized from Fusarium oxysporum with Weisella cibaria against cervical cancer cells. The study has done from 2022 to March 2023 in the food microbiology laboratory in the Department of Biology / College of Science / Mustansiriyah University. Lactic acid bacteria (LAB) were isolated from food sources (Turnip, Cabbage, Cauliflower), after serial steps from treated NaCl , then cultured in MRS (Man-Rogosa-Sharpe) broth, finally examined under a microscope. The antibacterial activity of Cell Free Supernatant (CFS) s that was produced by these isolates was detected to choose the best one and diagnosed by PCR and DNA sequencing. The nanoparticles (AgNo3) that were produced from Fusarium oxysporum by biosynthesis were obtained from higher studies laboratory for fungi, and these fungi was submitted to toxicity test. The Synergist effect of chosen LAB and Fusarium oxysporum nanoparticles was studied against cervical cancer cells. Results show that all food sources were rich in LAB and the best antibacterial activity was to turnip source and according to molecular diagnosis was Weisella cibaria , that recorded in NCBI as (MG7865551). The synergistic effect of W. cibaria and nanoparticles showed and decrease the cancer line viability rate after 72 hr. exposure to this effect.